2021
DOI: 10.1002/apj.2677
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe‐modified Mn–Ce–Fe–Co–Ox/P84 catalytic filter materials for low‐temperature NO removal synergistic Hg0oxidation

Abstract: A series of Mn–Ce–Fe–Co–Ox/P84 (polyimide) catalytic filter materials by in situ method (ISM) were investigated for the low‐temperature catalytic activities for NO and elemental mercury Hg0 in the simulated flue fixed‐bed system, especially under mixed atmosphere conditions with water and sulfur. The influence of Fe and Co doping ratio, Fe of loading sequence, and the types of precursors are systematically investigated under 8% H2O and 75 ppm SO2 atmosphere. Results showed that the toxic effects of H2O and SO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The gaseous NO reacts with -NH 2 forming N 2 and H 2 O, while simultaneously a strong inductive effect between Fe 3+ and V 4+ initiates a thermodynamically feasible redox reaction, regenerating the oxidation states for the consequent reduction cycles. In order to further validate these redox systems for NO x reductions, Shi et al 216 prepared a series of Mn-Ce-Fe-Co-O x /P84 (polyimide) catalytic filter materials to investigate the low-temperature catalytic activity of NO x , under mixed atmospheric conditions with water and sulfur. Activity of Mn-Ce-Fe-Co-O x in molar ratios of 4:5:1.25:1 achieved 81% NO x conversion at 170 °C.…”
Section: Novel Materials For Selective Catalytic Reduction (Scr) Of N...mentioning
confidence: 99%
“…The gaseous NO reacts with -NH 2 forming N 2 and H 2 O, while simultaneously a strong inductive effect between Fe 3+ and V 4+ initiates a thermodynamically feasible redox reaction, regenerating the oxidation states for the consequent reduction cycles. In order to further validate these redox systems for NO x reductions, Shi et al 216 prepared a series of Mn-Ce-Fe-Co-O x /P84 (polyimide) catalytic filter materials to investigate the low-temperature catalytic activity of NO x , under mixed atmospheric conditions with water and sulfur. Activity of Mn-Ce-Fe-Co-O x in molar ratios of 4:5:1.25:1 achieved 81% NO x conversion at 170 °C.…”
Section: Novel Materials For Selective Catalytic Reduction (Scr) Of N...mentioning
confidence: 99%
“…Recently, however, significantly novel materials and processes have been developed to efficiently accomplish mercury removal from air and water at plant scale 9–13 . Furthermore, much research has been done to oxidize the mercury vapour from Hg 0 to Hg 2+ to blunt its detrimental consequences on lungs and brain after inhalation 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Furthermore, much research has been done to oxidize the mercury vapour from Hg 0 to Hg 2+ to blunt its detrimental consequences on lungs and brain after inhalation. [14][15][16] To overcome the drawback of graphite erosion, the present work employs tubular packing of stainless steel SS-304 with tungsten carbide (WC) coated on its outer surface using indigenously developed laser-directed energy deposition (LDED) technique for application as a plausible alternative to conventional graphite packing. Meneghini and Bertin observed that the coating on outer surface of amalgam wettable material (here, SS-304) should be pure or compound carbide of electrically conducting transition metals such as titanium, zirconium, niobium, tantalum or tungsten.…”
Section: Introductionmentioning
confidence: 99%
“…The composite catalytic ber lter material (Shi 2021) is prepared by combining the catalytic technology with the lter material ber, the combined removal of dust, NO x and dioxins by existing dedusting equipment is one of the important ways to realize the low-cost and high-e ciency coordinated control of multi-pollutants in ue gas (Li 2014). The research emphasis of the composite catalytic ber lter material is the basic material and modi cation of the catalytic lter material.…”
Section: Introductionmentioning
confidence: 99%